Knowledge, attitude and practice relating to food supplement intake among Universiti Teknologi Mara (UiTM) Terengganu students / Nur Athirah Muhamad Sobri & Nurul Natasha Azira Shahrudin - Muhamad Sobri, Nur Athirah; Shahrudin, Nurul Natasha Azira (2017)
The research study paper is about determine the level knowledge, attitude and practices relating to food supplement intake among Universiti Teknologi Mara (UiTM) Terengganu students. Food supplement which is also known as dietary supplements are popular in so many countries including Malaysia. The data is available by the target population which is university students on their food supplement intake. The result o f the collecting data is obtained by 186 respondents and captured by using a set o f questionnaire with four sections. Since the university students has variety habits, characteristics or lifestyle, their intake o f food supplement may differ from the general population. The result reveal that the students have a lot o f knowledge about the food supplement intake and only a few o f them are not sure with the answer. They also have a good attitude and well practices towards food supplement intake. Food supplement also may be used in context o f healthy lifestyle or as compensate for unhealthy lifestyle. The design o f this research study is quantitative approach. This study investigate the effects o f three independent variables which are knowledge, attitudes, practice and dependent variable which is food supplement intake